1977
DOI: 10.1139/v77-084
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the condensation of lignins in alkaline media. Part II. The formation of stilbene and arylcoumaran structures through neighbouring group participation reactions

Abstract: JOSEF GIERER and INGEGERD PETTERSSON. Can. J. Chem. 55, 593 (1977). The alkaline condensation of p-hydroxyarylglycerol-a-aryl ether units in lignin with other phenolic structures and the subsequent reactions of the condensation products have been elucidated using appropriate model compounds. It is shown that the primary condensation of simple phenols (2,6-xylenol or resorcinol) into the a-position of phenolic compounds of the f3-aryl ether type is followed by an aryl participation (A,-3) reaction resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…The sulfonation of lignin under alkaline conditions and a high temperature was reported in the past. 44,45 Also, it should be highlighted that the sulfonate and carboxylate groups and total charge density of LS2 were higher than those of other samples. These results are in harmony with observed peaks of carboxylate and sulfonate groups in FTIR analysis.…”
Section: Charge Density and Hydrodynamic Diameter Characterizationmentioning
confidence: 92%
“…The sulfonation of lignin under alkaline conditions and a high temperature was reported in the past. 44,45 Also, it should be highlighted that the sulfonate and carboxylate groups and total charge density of LS2 were higher than those of other samples. These results are in harmony with observed peaks of carboxylate and sulfonate groups in FTIR analysis.…”
Section: Charge Density and Hydrodynamic Diameter Characterizationmentioning
confidence: 92%
“…Specifically, under acidic conditions, phenols were introduced at the aposition of lignin [94][95][96][97][98][99][100]. Phenolation can also occur under alkaline conditions, and the reaction mechanism is similar to that of condensation that occurs during kraft cooking [101,102]. Kobayashi et al [103][104][105] subjected kraft lignin to phenolation and observed a 2-2.5 times higher reactivity than that of unmodified kraft lignin.…”
Section: Phenolic Resinationmentioning
confidence: 99%
“…Thermally induced events possibly occurring within softwood kraft lignin operating via radical mechanisms at low temperatures. (Gierer 1980;Gierer and Pettersson 1977;Kawamoto et al 2007a;Kawamoto et al 2007b;Kawamoto et al 2008a;Kawamoto et al 2008b;Nakamura et al 2007;Ohashi et al 2011) At relatively low temperatures, radicals stabilized and trapped by steric factors within the solid structure of lignin (Sazanov and Gribanov 2010) may be activated (Scheme 2A). Phenoxy radicals can be generated via an H abstraction process when interacting with the thermally activated radicals (•R).…”
Section: Radical Coupling Mechanism Of Kraft Ligninmentioning
confidence: 99%
“…Since β-O-4 linkages have been reported to survive the kraft pulping process (Froass et al 1996;Jiang and Argyropoulos 1999;Jiang and Argyropoulos 1994;Liitiä et al 2003), the reported formation of formaldehyde at relatively low temperatures (Fenner and Lephardt 1981) can be explained by γ elimination of methylol (CH 2 -OH) groups within residual β-O-4 linkages in kraft lignin (Scheme 3A) (Gierer 1980;Gierer and Pettersson 1977) via quinone methide intermediates, which are readily formed from the phenoxy radicals derived from the phenolic OH groups. In addition to the elimination of the γ methylol (CH 2 -OH) group of the β-O-4 linkage creating a stable enol ether (Scheme 3A) (Gierer 1980;Gierer and Pettersson 1977;Kawamoto and Saka 2007), homolytic C β -O bond scission is a competing reaction pathway, responsible for the formation of two new phenoxy radicals (Scheme 3B) (Nakamura et al 2007).…”
Section: Radical Coupling Mechanism Of Kraft Ligninmentioning
confidence: 99%
See 1 more Smart Citation